'Austria First' revisited: a diachronic cross-sectional analysis of the gender and body politics of the extreme right. (27th May 2019) - Rheindorf, Markus; Wodak, Ruth
ABSTRACT: In this paper, Rheindorf and Wodak provide a discourse-historical analysis of extreme-right cultural politics in Austria, ranging from the blatant racism in the speeches of Vienna's former Deputy Mayor Johann Gudenus (now MP in the Austrian parliament) to the construction of an idealized national body in the election campaigns of the Freiheitliche Partei Österreichs (FPÖ), its programmatic agenda in handbooks and pamphlets, and the performances of far-right pop singer Andreas Gabalier. Rheindorf and Wodak argue that such cultural politics use a wide spectrum of discursive strategies both inside and outside established party politics and that the accompanying production of an ideal extreme-right subject is informed by nativist ideology. The cross-sectional analysis demonstrates that the cultural politics of the Austrian extreme right ranges from appropriated national symbols to coded National Socialist iconography. These politics pervasively construct a gendered and racialized national body, policed by a 'strict father' and nurtured by a 'self-sacrificing mother', vis-à-vis an apocalyptic threat scenario identified with migration, intellectual and political elites, cosmopolitanism and progressive gender politics.